JOB SATISFACTION AS THE PREDICTOR OF TEACHERS’ JOB PERFORMANCE IN KWARA STATE PUBLIC SECONDARY SCHOOLS - Warrah, Dr. Saleman Mashood; Binti Md Ngajib, Siti Hamira; Mustapha, Adam Ishola; Garba, Khadijah Wuraola (Selangor Humaniora Review, 2024)
Teachers' job satisfaction is fundamental in the actualization of educational objectives. Thus, the study examined job satisfaction as the predictor of teachers’ job performance in Kwara State Public Secondary Schools. The study adopted a quantitative research method. Simple random sampling technique was used to select 379 teachers. Four instruments were used to elicit information from respondents tagged salary questionnaire (SQ), promotion questionnaire (PQ), fringe benefits questionnaire (FBQ) and job performance questionnaire (JPQ). The instruments were subjected to reliability test using SPSS version 21 where reliability coefficient indicated at .840, .906, .856 and .785. Structural Equation Modeling (SEM) was used to analyze the hypotheses formulated. The findings revealed that salary has a significant relationship with job performance standardized regression weight of .803 and significant at p<0.05. The finding further found that promotion had a significant relationship with job performance with standardized coefficient of .992 and significant at p<0.05. The finding also reported that fringe benefits had a significant relationship with job performance with a standardized coefficient of 1.061 and significant at p<0.05. The findings concluded that job satisfaction is the predictor of teacher job performance. In line with the findings of the study, it was recommended that the policy makers as well as the government should improve teachers’ salary and promote them as and when due to perform their tasks excellently in the educational industry.